Effect of standard‐dose and high‐dose pimobendan on select indices of renal and cardiac function in dogs with American College of Veterinary Internal Medicine stage B2 myxomatous mitral valve disease. (13th September 2022) - Kaplan, Joanna L.; Visser, Lance C.; Gunther‐Harrington, Catherine T.; Ontiveros, Eric S.; Wittenburg, Luke A.; Palm, Carrie A.; Stern, Joshua A.
Abstract: Background: Pimobendan might have favorable effects on renal function but this has not been well‐studied in dogs with myxomatous mitral valve disease (MMVD). Objectives: Determine the effects of standard‐dose (SD_pimo) and high‐dose pimobendan (HD_pimo) on glomerular filtration rate (GFR) and cardiac size and function in dogs with preclinical MMVD. Animals: Thirty nonazotemic dogs with stage B2 MMVD. Methods: Prospective, randomized, double‐blinded, placebo‐controlled clinical study. Dogs had an echocardiographic examination, assessment of GFR (iohexol clearance), N‐terminal probrain natriuretic peptide (NT‐proBNP), and quality of life (QOL) score at baseline and 7 to 10 days after placebo (n = 6), SD_pimo 0.2 to 0.3 mg/kg q12 (n = 12), or HD_pimo 0.5 to 0.6 mg/kg q12h (n = 12). Results: No significant differences in GFR or QOL scores were detected between groups ( P ≥ .07). After HD_pimo, the mean [SD] percent change of NT_proBNP (−46.1 [20.2]%), left atrial volume (LAV; −27.1 [16.9]%), left ventricular end‐diastolic volume (EDV; −21.8 [15.0]%), and end‐systolic volume (ESV; −55.0 [20.7]%) were significantly different ( P ≤ .004) from placebo (0.5 [19.9]%, 1.3 [15.6]%, −0.2 [8.2]%, −7.3 [35.6]%, respectively) but not the percent change after SD_pimo (−36.6 [16.1]%, −22.7 [14.9]%, −16.7 [12.5]%, −41.6 [14.8]%, respectively; P > .05). After SD_pimo, percent change of NT_proBNP, LAV, EDV, and ESV were significantly different from placebo ( P < .05). Conclusions and Clinical Importance: Results suggest that pimobendan (SD_pimo or HD_pimo) might not affect renal function in nonazotemic dogs with stage B2 MMVD. High‐dose pimobendan did not demonstrate advantages over SD_pimo within the constraints of our study.